Ventilatory response to increasing body temperature: Characteristics and effect on central fatigue - Hayashi, K. (The Journal of Physical Fitness and Sports Medicine, 2015)
More than a hundred years ago, it was first reported that increases in body temperature stimulate minute ventilation. Since then, the characteristics, mechanisms and physiological meaning of this ventilatory response to increasing body temperature, so-called hyperthermia-induced hyperventilation, have gradually been uncovered. For example, it is now known that hyperthermia-induced hyperventilation has a core temperature threshold, like heat-dissipating responses (sweating and cutaneous vasodilation); but several factors affecting heat-dissipating responses do not influence the ventilatory response to increasing body temperature. On the other hand, evidence from several studies suggests there may be some relation between hyperthermia-induced hyperventilation and heat-dissipating responses. In addition, more recent evidence indicates that hyperthermia-induced hyperventilation may be related to central fatigue, which is considered to be one of the reasons exercise performance is diminished in heat. In fact, it has been suggested that hyperthermia-induced hyperventilation causes cerebral blood perfusion to be reduced, which decreases cerebral oxygenation and heat removal. This review presents an overview of the characteristics of the ventilatory response to increasing body temperature and its effect on central fatigue.